Indonesia Economic Prospects, June 2022 : Financial Deepening for Stronger Growth and Sustainable Recovery - World Bank (Washington, DC: World Bank, 2022)
Indonesia’s economic recovery from the Corornavirus (COVID-19) pandemic comes amidst an increasingly challenging global environment. Indonesia’s growth accelerated at the end of 2021 as the country stepped off from a devastating Delta wave in July-August, ending the year with 3.7 percent growth. The momentum carried into the first quarter of 2022 with the economy growing at 5 percent (yoy) and absorbing a short and sharp increase in Omicron-related COVID cases. Growth drivers since end 2021 have rebalanced gradually from exports and public consumption towards private consumption and investment. Since February, the war in Ukraine has disrupted the global economic environment with rising commodity prices and de-risking in global financial markets. The positive terms-of-trade effect has benefited Indonesia in the near-term through higher export and fiscal earnings. But the country is starting to feel the pressures of rising prices and tightening external finance.